'Grooming' and the sexual abuse of children institutional, Internet, and familial dimensions - McAlinden, Anne-Marie. (Oxford : Oxford University Press, 2013)
An inter-disciplinary, thematic, and empirical investigation of grooming in a multi-jurisdictional context, this book draws on extensive research in the form of over 50 interviews with professionals, working in sex offender assessment, management or treatment, as well as child protection, in the UK and the Republic of Ireland.
Series from CIP print record.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Includes bibliographical references and index.
Keywords: Child sexual abuse -- Great Britain; Child sexual abuse -- Ireland; Online sexual predators -- Great Britain; Online sexual predators -- Ireland